Perancangan Hotel Resort di Pantai Nusa Dua Selatan Bali dengan Tema Arsitektur Neo Vernakular - Francdy Santo Tampubolon (Jurnal Arsitektur Wastu Padma, 2023)
This research project focuses on the design of a Resort Hotel located on South Nusa Dua Beach, Bali. The main objective is to provide comfortable accommodation facilities for tourists, by making maximum use of the potential of the surrounding nature. In the design process, the theme Neo Vernacular Architecture was chosen. The choice of theme was based on the desire to highlight local Balinese architectural elements, which are oriented towards the utilization and preservation of the wealth of Bali's local environment. The main obstacle in this design is how to integrate the natural beauty of the beach with the needs of an effective and attractive tourist space for visitors. In addition, is the application of the Neo Vernacular theme which is packaged creatively in the architectural design of the hotel. In the discussion, it was found that the design solution lies in the arrangement of hotel rooms tailored to the specific functions of the resort, local characteristics, and the use of traditional Balinese layouts. Another discussion is that the shape of the roof of the building is designed following the example of local traditional housing to give an authentic touch.